Innovative Hr Strategies In Building A Culture Of Work Creativity - Satriadi Satriadi; Muhammad Sahid Dimitri; Prayoga Dwiguna; Nurul Syamsul Hayat; Saiful Anuar (International Journal of Management Research and Economics, 2025)
Human Resources have always been the most influential and important element in the development efforts of a nation and state. In the study of the literature has shown that using models based on open systems theory and concepts put forward by Schein can provide a holistic approach in describing organizational culture. This research aims to identify innovative strategies that can be used to build a culture of creativity and develop Human Resources (HR) skills that will assist organizations in facing the challenges of global business competition. In this study using the Systematic Literature method, the author collects data related to the theme, data search is carried out by looking for predetermined variable keywords. The conclusion in this study, we must pay attention to the selection of the right human resources who have an innovative spirit, enterprising, active learning and willing to work, forward orientation, many bright ideas, reasonable thinking and have good abilities in judging, managing time, efficiently, and the desire to be able to do experience.